2002
DOI: 10.1080/0142159021000002612
|View full text |Cite
|
Sign up to set email alerts
|

Effective faculty preceptoring and mentoring during reorganization of an academic medical center

Abstract: The experience and lessons learned in the design, implementation and initial evaluation of a demonstration faculty-to-faculty mentoring program, during a time of major institutional reorganization, are described. The question addressed was: Can a voluntary mentoring program be established with minimal resources and be effective in the context of major organizational change? Key design elements included two-tiered programs (one year preceptoring and multi-year mentoring), voluntary participation, and selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 25 publications
5
97
0
4
Order By: Relevance
“…The discomfort felt by mentees in the pilot program pairing process has also been observed in other studies (Zachary 2005, Gardiner 1999, Benson et al 2002. In the Flinders University mentoring program for early career female academics, an end of program survey revealed that a few mentees had an initial "fear of how to approach the partnership.…”
Section: An Individualised Process For Menteesmentioning
confidence: 87%
“…The discomfort felt by mentees in the pilot program pairing process has also been observed in other studies (Zachary 2005, Gardiner 1999, Benson et al 2002. In the Flinders University mentoring program for early career female academics, an end of program survey revealed that a few mentees had an initial "fear of how to approach the partnership.…”
Section: An Individualised Process For Menteesmentioning
confidence: 87%
“…The median (range) number of participants in the included studies was 18 (2-71), and all of the studies were conducted in North America. The nature of mentoring was not described in three studies, 24,30,31 four studies explored formal mentoring relationships, 23,26,28,29 , one study explored informal mentoring relationships 27 and one study provided participants with a definition of mentorship but did not describe if this was a formal process. 25 Most of the studies included participants of both genders.…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment of the articles (Appendix 4, online) revealed that most studies had clearly stated objectives, but the description of the sample and sampling procedures sometimes lacked detail. 23,24,27,28,31 Study findings were stated with varying levels of detail, and in one report it was difficult to discern the findings of the qualitative analysis. 23 We identified five major themes in relation to mentoring relationships: (1) desired characteristics and actions of the mentor and mentee, (2) initiation of mentoring relationships, (3) structure of mentoring relationships, (4) characteristics of mentoring relationships, and (5) barriers and possible solutions to mentoring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations